Nucleolar Localization Elements of Xenopus laevis U3 Small Nucleolar RNA - Lange, Thilo Sascha (The American Society for Cell Biology, 1998)
The Nucleolar Localization Elements (NoLEs) of Xenopus laevis U3 small nucleolar RNA (snoRNA) have been defined. Fluorescein-labeled wild-type U3 snoRNA injected into Xenopus oocyte nuclei localized specifically to nucleoli as shown by fluorescence microscopy. Injection of mutated U3 snoRNA revealed that the 5′ region containing Boxes A and A′, known to be important for rRNA processing, is not essential for nucleolar localization. Nucleolar localization of U3 snoRNA was independent of the presence and nature of the 5′ cap and the terminal stem. In contrast, Boxes C and D, common to the Box C/D snoRNA family, are critical elements for U3 localization. Mutation of the hinge region, Box B, or Box C′ led to reduced U3 nucleolar localization. Results of competition experiments suggested that Boxes C and D act in a cooperative manner. It is proposed that Box B facilitates U3 snoRNA nucleolar localization by the primary NoLEs (Boxes C and D), with the hinge region of U3 subsequently base pairing to the external transcribed spacer of pre-rRNA, thus positioning U3 snoRNA for its roles in rRNA processing.